2019
DOI: 10.1002/anie.201901141
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin Protein HP1α Gelation Dynamics Revealed by Solid‐State NMR Spectroscopy

Abstract: Heterochromatin protein 1a (HP1a)u ndergoes liquid-liquid phase separation (LLPS) and forms liquid droplets and gels in vitro,p roperties that also appear to be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…[5,6] For instance, binding of the IDR-containing heterochromatin protein HP1α to the histone H3K9 methylation site induces LLPS in specific domains of heterochromatin. [8][9][10][11] LLPS also occurs in euchromatin regions that are rich in acetylated histone tails when the transcriptional regulator protein BRD4, which contains a long IDR, is co-localized. [12,13] Thus, the nature of the relationship between LLPS-mediated chromatin-condensation and proteins is gradually determined.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] For instance, binding of the IDR-containing heterochromatin protein HP1α to the histone H3K9 methylation site induces LLPS in specific domains of heterochromatin. [8][9][10][11] LLPS also occurs in euchromatin regions that are rich in acetylated histone tails when the transcriptional regulator protein BRD4, which contains a long IDR, is co-localized. [12,13] Thus, the nature of the relationship between LLPS-mediated chromatin-condensation and proteins is gradually determined.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, direct insights into the structural and dynamical organization of liquid-like droplets has been limited 12 . Instead, solid-state NMR (ssNMR) has been employed to study formation 13,14 and structural organization 13,1519 of protein hydrogels and fibrillar assemblies that may be closely related to LLPS 3,20 . For example, we have previously used ssNMR to investigate the hydrogel state of the FG repeat domain of the nucleoporin Nsp1p, revealing that transient amyloid-like β-sheet interactions among NTQS-rich protein regions are responsible for gelation and network formation 13,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Single cell sequencing has convincingly shown that nucleosome positioning is not consistent between cells in a population (30)(31)(32). Heterochromatin domains comprising phase-separated droplets are now known to be more dynamic than previously assumed (33,34). Chromatin interactions are similarly variegated: the frequency of DNA loop formation is approximately 30% of alleles at maximum depending on the locus and RNAPII-mediated loops are heterogeneous (35)(36)(37).…”
Section: Small Variable Domains Of Chromatin Structure Facilitate Heterogeneity and Inducibilitymentioning
confidence: 99%